2011
DOI: 10.1016/j.jacc.2010.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Comparison of Drug-Eluting Stents and Coronary Artery Bypass Grafting for Multivessel Coronary Revascularization

Abstract: For patients with multivessel disease, DES treatment, compared with CABG, showed similar rates of mortality and of the composite safety outcomes, but higher rates of revascularization up to 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The findings of these studies are consistent with ours because the relative outcomes associated with the two procedures were similar across quartiles [1] or quintiles [17] of PS or terciles of EuroSCORE and SYNTAX Score [4] . The categorization adopted in these studies may, however, have been too broad to unveil the heterogeneity of treatment-effect estimates [18,19] , while the one adopted here should yield stronger evidence.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings of these studies are consistent with ours because the relative outcomes associated with the two procedures were similar across quartiles [1] or quintiles [17] of PS or terciles of EuroSCORE and SYNTAX Score [4] . The categorization adopted in these studies may, however, have been too broad to unveil the heterogeneity of treatment-effect estimates [18,19] , while the one adopted here should yield stronger evidence.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of severe Coronary Artery Disease (CAD) (left main or multivessel involvement) -the scientific evidence [1][2][3][4][5][6][7][8][9] supporting the interventional choice between Percutaneous Coronary Intervention (PCI) and Coronary Artery Bypass Graft (CABG) is inconclusive. Uncertainty surrounds not only the 'best' technique in absolute terms (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,[7][8][9][10] Clinical registry and trials data have shown a repeat revascularization rate of ≈5% at 5 years after surgery, 10 but these prior studies were limited in size, types of centers, and duration of follow-up. 1,7,8,10,11 Over an 18-year time frame, the present study was able to document a low rate of repeat revascularization after CABG among patients aged ≥65 years. Fewer than 10% of CABG patients required a repeat revascularization procedure within 5 years and 13% within 10 years; only 1 in 6 patients who survived 18 years underwent a repeat procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, data from SYNTAX and CARDia and from nonrandomized comparisons [21,22] demonstrate equivalent short-term mortality of PCI with DES and CABG in patients with diabetes, except for patients with the most complex disease (SYNTAX score ≥33) [19]. Importantly, follow-up at 1-year may not yet reflect the true long-term differences between CABG and DES treatment of patients with DM because previous reports demonstrated reduced long-term mortality in CABG compared with PCI [17,18].…”
Section: Cabg Versus Pci In Multivessel Cadmentioning
confidence: 99%